Strategi Efektif Pembelajaran Ilmu Sharf : Integrasi Nisbah, Tasghir, Dalam Kelas Bahasa Arab - Firdaus, Fedi Agniar (AL MA'ANY, 2025)
This study explores the effectiveness of the Sharaf Science learning strategy with a focus on integrating the concepts of nisbah and tasghir in Arabic language classes. The method used is a mixed-methods with a qualitative dominance, which includes classroom observation, in-depth interviews with teachers and students, and analysis of teaching materials. The qualitative results are used as the basis for developing an integrative learning module. Furthermore, the quantitative stage uses a quasi-experimental design with a pre-test and post-test design to assess the impact of the module on students' morphological understanding.The findings show that the main challenges in learning nisbah and tasghir include the complexity of morphological patterns, traditional teaching methods that are less interactive, and the limited use of digital technology. To overcome this, a learning strategy that combines collaborative learning, word games, the use of visual media, and digital applications has been shown to improve students' motivation and understanding. The application of technology—such as interactive platforms and audio-visual media—helps students understand morphological concepts contextually. In addition, regular formative assessments provide constructive feedback that encourages improvements in the learning process. In conclusion, the integration of nisbah and tasghir through an innovative and technology-oriented pedagogical approach can increase student engagement and deepen Arabic language understanding. The recommendations of this study include teacher training to adopt interactive methods and the development of contextual learning resources so that the objectives of learning Sharaf Science are achieved optimally